Policy Measures for Mitigation and Adaptation in Cattle Production Systems in the Humid and Subhumid Tropics of Latin America - Ibrahim, Muhammad Akbar (2013)
En: Proceedings of the Symposium on Mitigating Greenhouse Gas Emissions from Animal Production: a Policy Agenda. Asunción, Paraguay, 6-7 May 2009